Analysis of CSR Performance and Welfare of PT NHM's Mining Circle Community - Lesmana, Denny; Sirat, Abdul Hadi; Soleman, Marwan Man (Jurnal Manajemen Bisnis, 2023)
This study analyzes PT NHM's CSR performance and the factors that support its implementation for the welfare of mining communities. CSR programs, including PPM and HRP, have a positive impact by improving income, education, health, housing, environment, and socio-cultural aspects. PT NHM's CSR performance is measured by the achievement of the PPM program in 2021, reaching 127% of the planning target, indicating satisfactory performance. Success factors for CSR programs include supportive company policies, good relationships with stakeholders, effective CSR performance, and improvement of CSR programs. This research is a descriptive qualitative research with data collection through interviews with 25 selected informants. In order to improve the welfare of the community around the mine, PT NHM has implemented a CSR program that focuses on providing benefits that are directly felt by the community, especially through the philanthropic HRP program. This proves the company's commitment in supporting the development and welfare of the local community. In conclusion, PT NHM's CSR performance is very positive, supported by the factors mentioned, and has the potential to have a sustainable positive impact on the communities around the mine.